Tutela coletiva dos direitos individuais homogêneos: os limites da legitimidade das associações civis - Isabela Campos Vidigal (2014)
The present work will analise the standing limits of civil associations in defense of homogeneous individual rights, aiming thus contribute to overcome the large existing legal uncertainty, because doctrine and jurisprudence dispute whether the associations could only defend the homogeneous individual rights of his associates or any citizen who is a holder of a right similar to the object of collective action. For this and considering that the collective process is an instrument appropriate to the defense of collective rights and to the collective defense of individual rights, will be promoted a study about the nature and specificities of homogeneous individual rights which in attention to the demands of a differentiated and appropriate jurisdiction, consist in the main element to the conformation of the procedural rules , beyond the critical examination of the grounds relied on by the Courts, which will therefore be the guiding thread for the answer to the problem under investigation. Thus, it is expected to assist in developing and maturing of collective process, that this goal can only be achieved through the settlement of the specific conceptual premises of collective actions, which can never be separated from the nature of the rights protected. Moreover, the objective is to encourage the filing of claims by civil associations, which, being one of the most democratic forms of collective advocacy (and collective rights), must always be committed to their real purposes before the law.